microRNA-9 Inhibits Vulnerable Plaque Formation and Vascular Remodeling via Suppression of the SDC2-Dependent FAK/ERK Signaling Pathway in Mice With Atherosclerosis - Zhang, Ruihong; Song, Beibei; Hong, Xiaojian; Shen, Zhiyuan; Sui, Li; Wang, Siyu (Frontiers in Physiology, 2020)
microRNAs (miRNAs or miRs) play important roles in modulating the occurrence and progression of atherosclerosis and acute coronary syndrome (ACS). Herein, this study aimed to investigate the possible role of miR-9 in the development of atherosclerosis. Initially, the differentially expressed genes associated with ACS were screened and miRNAs that regulate syndecan-2 (SDC2) were predicted using microarray analysis. Furthermore, the biological functions of miR-9 and SDC2 on aortic plaque area, proliferation of collagen fibers, Mac-3-labeled macrophages, inflammatory response, and levels of the focal adhesion kinase/extracellular signal-regulated kinase (FAK/ERK) signaling pathway-related proteins in atherosclerosis were evaluated after ectopic miR-9 expression or SDC2 depletion in ACS mice using oil red O staining, Masson’s trichrome staining, immunohistochemistry, and Western blot analysis, respectively. SDC2 was highly-expressed, while miR-9 was poorly-expressed in atherosclerosis. Additionally, miR-9 targeted SDC2 and negatively-regulated its expression. Up-regulation of miR-9 reduced aortic plaque area, the proliferation of collagen fibers, Mac-3-labeled macrophages and levels of IL-6, IL-1β, and TNF-α by suppressing SDC2 and the FAK/ERK signaling pathway, thereby ameliorating atherosclerosis in ACS mice. In conclusion, the current study provides evidence that miR-9 retards atherosclerosis by repressing SDC2 and the FAK/ERK signaling pathway, highlighting a new theoretical basis for the treatment of atherosclerosis.